How Metabolomics Provides Novel Insights on Celiac Disease and Gluten-Free Diet: A Narrative Review - Vacca, Mirco; Porrelli, Annalisa; Calabrese, Francesco Maria; Lippolis, Tamara; Iacobellis, Ilaria; Celano, Giuseppe; Pinto, Daniela; Russo, Francesco; Giannelli, Gianluigi; De Angelis, Maria (Frontiers in Microbiology, 2022)
Celiac disease (CD) is an inflammatory autoimmune disorder triggered by the ingestion of gluten from wheat and other cereals. Nowadays, its positive diagnosis is based on invasive approaches such as the histological examination of intestinal biopsies and positive serology screening of antibodies. After proven diagnosis, the only admissible treatment for CD individuals is strict life-long adherence to gluten-free diet (GFD), although it is not a conclusive therapy. Acting by different mechanisms and with different etiologies, both CD and GFD have a great impact on gut microbiota that result in a different taxa composition. Altered production of specific metabolites reflects these microbiota changes. In this light, the currently available literature reports some suggestions about the possible use of specific metabolites, detected by meta-omics analyses, as potential biomarkers for a CD non-invasive diagnosis. To highlight insights about metabolomics application in CD study, we conducted a narrative dissertation of selected original articles published in the last decade. By applying a systematic search, it clearly emerged how the metabolomic signature appears to be contradictory, as well as poorly investigated.